Applying Rigorous Impact Evaluation in GIZ Governance Programmes: Results of a GIZ Initiative on Impacts in Governance - von Schiller, Armin (GIZ GmbH, 2020)
Pressure is mounting on international development cooperation agencies to prove the impact of their work. Private and public commissioners as well as the general public are increasingly asking for robust evidence of impact. In this context, rigorous impact evaluation (RIE) methods are increasingly receiving attention within the broader German development system and in GIZ. Compared to other implementing agencies such as DFID or USAid, the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH has so far relatively little experience in systematically applying rigorous methods of impact evaluation. This is particularly true in the governance sector. In order to gain more experience and to understand which methods and formats are best suited for GIZ governance programmes, the Governance and Conflict division and the Africa department launched the ‘Impact Initiative Africa’ in 2016, a cooperative effort with several programmes in Africa. The Initiative set out to apply the experiences from GIZ governance programmes to design and conduct RIEs, and to use the results to steer programme implementation. Initially, the Initiative included three countries: Benin (Programme for Decentralisation and Local Development), Malawi (Support to Public Financial and Economic Management) and Mozambique (Good Financial Governance in Mozambique). During its implementation, the Initiative also benefitted from the experience of two additional governance programmes which had already undertaken RIEs, namely Peru (Citizen-oriented State Reform Programme) and Pakistan (Support to Local Governance Programme II). This report summarizes the insights gained from these experiences and discusses opportunities and limitations regarding the use and usability of RIEs in GIZ governance programmes as well as proposals on how to organise RIEs to maximise learning potential and benefits for the specific programmes and the GIZ Governance sector at large.

Evaluating CLARISSA: Innovation Driven by a Participatory Learning Agenda - Apgar, Marina; Snijder, Mieke; Kakri, Shanta; Macleod, Shona; Paul, Sukanta; Sambo, Anna; Ton, Giel (CLARISSA working paper, 2020)
Children end up in child labour as a result of many, often unknown or hidden, interactions between multiple actors and multiple factors within households, communities, and labour systems, leading to unpredictable outcomes for children and other sector stakeholders and sometimes resulting in the worst forms of child labour (WFCL). It is a complex problem, and interventions aimed at tackling it are also, inevitably, complex and challenging. The way they influence change is non-linear, causality is uncertain, and unintended consequences may result. Programmes such as the Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) that are engaging with such intractable challenges and aim to reach the most left behind (children in WFCL) are operating in conditions of complexity. This complexity poses significant challenges to the way programmes are designed, planned, implemented, and evaluated, and requires a move away from linear and predetermined models. In this Working Paper, we share our experience and early learning about how to design and implement monitoring, evaluation and learning that intentionally embraces the challenge of complexity.